Impact of HLA Epitope Matching on Outcomes After Unrelated Bone Marrow Transplantation - Iwasaki, Makoto; Kanda, Junya; Tanaka, Hidenori; Shindo, Takero; Sato, Takahiko; Doki, Noriko; Fukuda, Takahiro; Ozawa, Yukiyasu; Eto, Tetsuya; Uchida, Naoyuki; Katayama, Yuta; Kataoka, Keisuke; et al. (Frontiers in Immunology, 2022)
The significance of antibody-identified epitopes stimulating humoral alloimmunity is not well understood in the identification of non-permissive HLA mismatching patterns in hematopoietic stem cell transplantation (HSCT). This was a retrospective study in a cohort of 9,991 patients who underwent their first HSCT for hematologic malignancies from unrelated bone marrow donors in the Transplant Registry Unified Management Program (TRUMP). HLA eplet mismatches (EMM) were quantified using HLAMatchmaker (HLAMM). The median age of patients was 48 years (range, 16 to 77). The number of EMM in recipient-donor pairs in our study population ranged from 0 to 37 in HLA class I (median, 0) and 0 to 60 in HLA class II (median, 1). In addition to the known high-risk mismatch patterns in the Japanese cohort, HLA-C EMM in the GVH direction was associated with a significantly higher risk for grade III-IV aGVHD, leading to a higher risk of non-relapse mortality and lower overall survival (compared with HLA-C matched patients, HR 1.67, 95% CI 1.44–1.95; HR 1.39, 95% CI 1.25–1.54; HR 1.20, 95% CI 1.10–1.30, respectively). HLAMM-based epitope matching might be useful for identifying patients who are at high risk for serious complications after HSCT from HLA mismatched unrelated donors.